Management of vascular trauma across Canada: A cohort study with implications for practice. Issue 5 (May 2022) - Smith, Shane; Allen, Laura; Khwaja, Kosar; Joos, Emilie; Ball, Chad G; Engels, Paul T; Naji, Faysal; Lampron, Jacinthe; Widder, Sandy; Minor, Sam; Jessula, Samuel; Parry, Neil G; et al.
Highlights: With the evolution of vascular trauma management, it is important to know who is treating these patients, and how injuries are identified and managed. The primary goal of this study is the description of the incidence of injury to named vessels in the Canadian trauma patient population. Variability in injury mechanism, management, specialty responsible for management, and outcomes have implications for practice change and knowledge translation. Abstract: Background: The aim of this study was to provide a description of vascular trauma and its management at trauma centers across Canada. Methods: This retrospective cohort study evaluated patients from 8 Canadian level 1 trauma centers (2011–2015). Medical records were queried to identify adult patients who survived to hospital with major vascular injury. Major vascular injury was defined as injury to named arterial or venous vessels in the legs, arms torso, and neck. Data collected included patient demographics, injury mechanism, injury details, management and clinical outcomes. Results: A total of 1330 patients were included. Patients were 76% male with a mean age of 43 (SD 18.8). Reported injuries were 63% blunt, 36% penetrating, and the remainder mixed. The most common specific mechanisms of injury were motor vehicle collision (36%), stabbing (26%), and falls (16%), with gunshot injuries accounting for <5%. Pre-hospital tourniquets were applied in 27 patients (2%). The mean Injury Severity Score (ISS) was 24 (SD 14.5). We identified injuries to named vessels of the neck (32%), thorax (23%), abdomen and pelvis (27%), upper extremity (14%) and lower extremity (10%). Specific vascular injuries included transection (50%), complete occlusion (11%), partial occlusion (39%), and pseudoaneurysm formation (11%). Injuries were managed non-operatively in 32%, with definitive open surgical management (24%), endovascular management (9%) and with damage control techniques in the operating room (3%). Amputation occurred in 10% of lower extremity and 5% of upper extremity injuries. Responsibility for vascular injury management was undertaken by a wide variety of specialists ( n  = 17). Overall, in-hospital mortality was 13%, and 2% of patients underwent amputation. Conclusion: This study describes the nature and management of vascular injuries across Canada. The variability in injury mechanisms, management strategies, specialty responsible for management, and outcomes have important implications for practice change and knowledge translation.